2014
DOI: 10.15252/embj.201387605
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐133 promotes cardiac reprogramming by directly repressing Snai1 and silencing fibroblast signatures

Abstract: Fibroblasts can be directly reprogrammed into cardiomyocyte-like cells (iCMs) by overexpression of cardiac transcription factors or microRNAs. However, induction of functional cardiomyocytes is inefficient, and molecular mechanisms of direct reprogramming remain undefined. Here, we demonstrate that addition of miR-133a (miR-133) to Gata4, Mef2c, and Tbx5 (GMT) or GMT plus Mesp1 and Myocd improved cardiac reprogramming from mouse or human fibroblasts by directly repressing Snai1, a master regulator of epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
277
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 283 publications
(285 citation statements)
references
References 29 publications
7
277
0
1
Order By: Relevance
“…These stimulated cells expressed cardiac specific proteins and showed spontaneous contractility, emphasizing the role of these miRs in the control of specific cell development programs via the modulation of specific factor targets. Further, both human and mouse fibroblasts can be reprogrammed to form cardiomyocyte-like cells by overexpression of cardiac transcription factors (Gata4, Mef2c, and Tbx5 (GMT) or GMT plus Mesp1 and Myocd) along with miR 133a, which directly represses Snai1 which normally regulates EMT processes [16] . Interestingly, exogenous miR133b can also downregulate Snai1 expression, suppressing fibroblast genes and upregulate the expression of a number of characteristic cardiac cell genes in vitro, yet it cannot replace miR133a during normal heart development in vivo.…”
Section: Cardiac Myogenesismentioning
confidence: 99%
“…These stimulated cells expressed cardiac specific proteins and showed spontaneous contractility, emphasizing the role of these miRs in the control of specific cell development programs via the modulation of specific factor targets. Further, both human and mouse fibroblasts can be reprogrammed to form cardiomyocyte-like cells by overexpression of cardiac transcription factors (Gata4, Mef2c, and Tbx5 (GMT) or GMT plus Mesp1 and Myocd) along with miR 133a, which directly represses Snai1 which normally regulates EMT processes [16] . Interestingly, exogenous miR133b can also downregulate Snai1 expression, suppressing fibroblast genes and upregulate the expression of a number of characteristic cardiac cell genes in vitro, yet it cannot replace miR133a during normal heart development in vivo.…”
Section: Cardiac Myogenesismentioning
confidence: 99%
“…1 Subsequently, multiple groups have achieved and improved direct cardiac reprogramming from mouse and human fibroblasts by overexpressing other combinations of cardiac transcription factors and cardiac-enriched miRNAs. [2][3][4][5][6][7][8][9] Intriguingly, it was reported that gene delivery of reprogramming factors into mouse infarcted hearts converted endogenous CFs into functional iCMs, reduced scar size, and improved cardiac function after myocardial infarction. 4,10,11 Although these recent achievements are promising, the low reprogramming efficiency of fully reprogrammed functional iCMs and the reproducibility of cardiac reprogramming continue to be controversial aspects of this technology.…”
mentioning
confidence: 99%
“…Furthermore, we found that miR-133-mediated Snai1 repression was critical for cardiac reprogramming in adult mouse (and human cardiac) fibroblasts, and that silencing fibroblast signatures via miR-133/Snai1 was a key molecular roadblock during cardiac reprogramming. 18) Importantly, this is a first study demonstrating a molecular mechanism underlying cardiac reprogramming by defined factors. Generation of human iCMs: In 2013, three studies including ours applied the concept of direct reprogramming to neonatal and adult human fibroblasts.…”
Section: Direct Cardiac Reprogramming In Vitromentioning
confidence: 85%